2000
DOI: 10.1097/00006534-200004050-00006
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Burns after Treatment with 670Nanometer Low-Power Laser Light

Abstract: Recent investigations have reported contradictory results on the influence of low-power laser light on wound healing. Low-power laser with a power output of 250 mW and an emitted laser light of 670 nm have been insufficiently investigated to date. The effect of a 250-mW/670-nm laser light on the healing of burning wounds in rats was investigated. Thirty rats were burned on both flanks. One wound was irradiated with 670-nm laser light (2 J/cm2), whereas the other side remained untreated. Macroscopic evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
3
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 18 publications
3
41
3
2
Order By: Relevance
“…While some reports show encouraging experimental and clinical data, other investigators found no improvement in wound healing processes and were not able to reproduce the above-mentioned effects after light irradiation [4,7,13,19,20].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While some reports show encouraging experimental and clinical data, other investigators found no improvement in wound healing processes and were not able to reproduce the above-mentioned effects after light irradiation [4,7,13,19,20].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Hunter et al were unable to demonstrate a clinically significant acceleration of wound healing in partial thickness wounds of pigs treated with laser therapy [7]. Other investigators were also unable to reproduce the above-mentioned therapeutic effects in wound healing processes [4,13,19,20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This system is basically dependent on specific selected parameters which are: the inflammatory cells, the collagen deposition, the angiogenesis and the granulation tissue (Table 1) [10,27,28]. The extent of collagen deposition was qualitatively evaluated by MT stain, while the other parameters were qualitatively assessed using H&E stained sections.…”
Section: Morphometric Studymentioning
confidence: 99%
“…Rats in the two laser-treated groups (n = 15 each) were exposed daily to 38.2 J/cm 2 or 76.4 J/cm 2 LLLT, respectively, from day 1 after burning until the experimental time period was completed. The burned tissues daily received a certain amount of laser energy [12][13][14][29][30][31] during the wound healing process in order to increase reparative activities. The specifications of the laser (manufactured by Iranian Atomic Energy Agency; Tehran, Iran) are shown in the Table. To apply the laser treatment, we divided the burned area into several equal squares (1 × 1 cm).…”
Section: Study Groupsmentioning
confidence: 99%